The impact of data sonification in virtual reality robot teleoperation - Bremner, Paul; Mitchell, Thomas J.; McIntosh, Verity (Frontiers in Virtual Reality, 2022)
Virtual Reality (VR) is being increasingly used to provide a more intuitive and embodied approach to robotic teleoperation, giving operators a sense of presence in the remote environment. Prior research has shown that presence can be enhanced when additional sensory cues such as sound are introduced. Data sonification is the use of non-speech audio to convey information, and in the context of VR robot teleoperation it has the potential to reduce cognitive load, by spreading data between sensory modalities, increase an operator's sense of presence and, consequently, improve task performance. Here we present a novel study methodology to investigate how the design of data sonification impacts on these important metrics and other key measures of user experience, such as stress. We examine a nuclear decommissioning application of robotic teleoperation where the benefits of VR in terms of spatial reasoning and task performance are desirable. However, as the operational environment is hazardous, a sense of presence may not be desirable as it can lead to heightened operator stress. We conduct a study in which we compare the effects of diegetic sounds (literal and established sonifications) with abstract sounds (non-established sonifications). Our findings show that the diegetic sounds decrease workload, whereas abstract sounds increase workload, and are more stressful. Additionally, and contrary to expectations, sonification does not impact presence. These findings have implications for the design of sonic environments in virtual reality.